Analisis Fraud Triangle Dalam Mendeteksi Financial Statement Fraud(Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Haryono, Mukhlis Eko, Dr. Noer Sasongko, S.E., M.Si., AK., CA (2017)
The aim of this research is to analyze the influence of Fraud Triangle in detecting phenomenon of financial statement frauds. In this research there are 7 variables that are hypothesized to affect fraud. These variables derive from the 3 element of fraud triangle, they are Financial Stability, Personal Financial Need, External Pressure, Financial Targets (from pressure), Nature of Industry, Effective monitoring (from opportunity), and Total Accruals to Total Assets (from rationalization). The population of this research were manufacture companies listed in Indonesia Stock Exchange IDX) 2012-2014. The Research used purposive sampling technique and found 25 companies, with 3 years of observation. Thus, the total number of sample studied was 75. In this research, the hypothesis were analyzed using logistic regression analysis. The results indicate that Personal Financial Need, Nature of Industry, Total Accruals to Total Assets have a significant influence on financial statement fraud. Meanwhile, Financial Stability, External Pressure, Financial Targets, Effective Monitoring do not have significant influence on financial statement fraud. Keywords:Fraud, Opportunity, Pressure, Rationalization